Effect of organic manure on wheat under drought stress condition - Hassan, M; Amin, AKM Ruhul; Rabbi, M H H; Mahmud, M D; Hossain, M D (SAARC Journal of Agriculture, 2023)
A pot experiment was conducted at the net house of Sher-e-Bangla Agricultural University, Dhaka during 2017-18 of rabi season to evaluate the impact of organic manure to combat drought stress of wheat. The experiment was laid out in a Completely Randomized Design (CRD) with three replications. Factor A: Different organic manure [F0 = Control, F1 = Cow dung 10 t ha-1, F2 = Vermicompost 7 t ha-1] and Factor B: Drought in different growth stages [D0 = Control, D1 = Drought in crown root initiation stage (20-29 DAS), D2 = Drought in booting stage (45-54 DAS), and D3 = Drought in anthesis stage (55-64 DAS)]. BARI Gom-28 variety of wheat was used as test crop. Significant variation was observed on growth, yield and yield contributing parameters. In the case of interaction, the maximum plant height (27.66, 48.10, 63.15 and 78.56cm, respectively) at 20, 40, 60 DAS and at harvest; highest number of effective tillers plant-1 (10.33), spike length (16.12 cm), number of spikelet spike-1 (17.40), number of grains spikelet-1 (2.85), number of grains spike-1 (49.59), weight of 1000 seed grain (48.37 g), grain yield (4.89 g plant-1), straw yield (5.18 g plant-1), biological yield (10.07 g plant-1) and harvest index (48.56%) were recorded from cow dung 10 t ha-1 with control treatment. It can be concluded that application of cow dung is effective in wheat crop to mitigate drought condition. SAARC J. Agric., 21(1): 175-188 (2023)